Experimental investigation on effects of water-based ultrasonic vibrations, transverse magnetic field and water temperatures on percussion laser drilling performance. (15th April 2019) - Wang, Houxiao; Zhu, Sukai; Xu, Ye; Ren, Naifei
Highlights: A water-based magnetic-ultrasonic assisted laser drilling technology is reported. Magnetic-ultrasonic assistance effectively improves laser drilling performance. Water temperature slightly affects hole formation, microstructure and hardness. Ultrasonic assistance with high water temperature greatly relieves residual stress. Abstract: A novel magnetic-ultrasonic assisted laser drilling technology, which integrates and couples water-based ultrasonic vibrations with an external transverse magnetic field for assisting the process of percussion laser drilling, is reported to carry out laser drilling experiments for improving hole drilling performance. The influence of water temperature on drilling performance for water-based magnetic-ultrasonic assisted percussion laser drilling technology is first reported. The influential mechanisms and roles of magnetic assistance and/or water-based ultrasonic assistance on the process and performance of percussion laser drilling were analysed, including both blind hole and through hole drilling. The effects of water-based ultrasonic vibrations and/or magnetic assistance on laser drilling performance were systematically studied via corresponding comparisons. It was demonstrated that the couple magnetic-ultrasonic assistance effectively increased laser drilling performance, by increasing laser energy absorption efficiency inside a drilling hole, enhancing material removal, increasing drilled depth, reducing recast layer formation and hole taper, improving microstructure and micro hardness performance, and relieving residual stress. Besides, it was reported that the uniform mechanical vibrations induced by water-based ultrasonic assistance effectively relieved residual stress (65.8% reduction) for the drilled specimen. The addition of an external transverse magnetic field could further relieve residual stress with a reduction percentage of 89.1%, resulting from the coupled magnetic-ultrasonic assistance. In addition, the water medium with a relatively high temperature was helpful for decreasing residual stress on the drilled sample. The alteration of water temperature (from 33.9 °C to 64.2 °C) not only greatly changed the value but also changed the direction of the residual stress (hole entrance: changing from −163 MPa to +32 MPa; hole exit: changing from −284 MPa to +64 MPa). However, the water temperature showed small effects on microstructure, micro hardness, recast layer thickness, hole cross-section, hole circularity deviation, and hole taper angle.